Trisomy 18 Case, with and without Cardiac Surgery - Herlina Dimiati; Cut Nanda Feby Ayulinda (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Trisomy 18, known as Edwards Syndrome, is the second-largest chromosomal disorder with a poor prognosis with the survival rate from 5 to 10% at one year of age. The most common factors underlying death are congenital heart defects, heart failure, and pulmonary hypertension. Cardiac surgery performed to patients with Trisomy 18 is associated with a reduction of mortality. This case report presents two cases of Trisomy 18, in which one of them underwent cardiac surgery.